New Normal in higher education for the post-COVID-19 world: Reimagining and reexamining factors for student success in online learning - Hungwei Tseng; Chris Inman (Online Learning)
As the novel coronavirus began to rapidly spread worldwide in March 2020, emergency transitions to the remote education processes were adopted in all institutions so as not to interrupt students’ learning. In this study, we intended to investigate to what extent do factors of online course design and student learning impact students’ success after online student characteristics are controlled. Online survey data were collected from 182 undergraduate and graduate students enrolled in at least one fully online course(s). The results revealed that a student’s online learning experience was a critical factor in determining the students’ attitudes when facing future online courses that were diverse and required autonomy, as well as the student’s ability to adapt to challenges from online courses that might utilize multiple information and communication technology (ICT) tools. Moreover, time management, course design/structure and quality facilitation, and emotional presence were consistently found to be significant determinants of student’s online learning success.